Feasibility of The Enrichment Module of Biodiversity Utilization Based on Medicinal Plants Sub-Material - Musriati, Ayu; Syamswisna, Syamswisna; Titin, Titin (Universitas Islam Negeri Walisongo Semarang, 2024)
Students' abilities in the learning process are, of course, different, so the grades obtained are also different. Enrichment modules are used as alternative teaching materials for students with more abilities and have achieved minimum completeness criteria to increase and deepen knowledge about local potential. The enrichment module created presents the use of biodiversity, especially medicinal plants in Tirta Kencana Village, Bengkayang Regency, so that students can get to know the types of medicinal plants and their benefits and how to process them. This research aims to test the feasibility of the submaterial enrichment module for utilizing biodiversity. The method used is Research and Development (R&D) with the Borg and Gall model. The enrichment module was validated by 5 validators at SMA, namely 2 lecturers and 3 biology teachers. Data analysis using the Lawshe formula obtained a CVI value of 0.99 so that the enrichment module was declared valid or suitable for use as teaching material in the learning process on the sub-material of using biodiversity